2022
DOI: 10.1111/os.13223
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Rhombic and Inverted Triangle Configurations of Cannulated Screws on Internal Fixation of Nondisplaced Femoral Neck Fractures in Elderly Patients

Abstract: Objective To investigate whether four‐screw fixation in rhombic configuration could improve the clinical outcomes and decrease the complication rate compared with three‐screw fixation in inverted triangle configuration in elderly patients with nondisplaced femoral neck fractures. Method From January 2018 to January 2019, 91 elderly patients with nondisplaced femoral neck fractures who were treated with a cannulated screw system were reviewed retrospectively. The inverted triangle configuration was applied in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A number of studies have since shown that it is a poor predictor of non-union [25]. However, others, such as the study by Zhu et al [26], have found it useful in predicting reoperation after initial fixation. The Dutch Surgical Society guidelines for the treatment of femoral neck fractures are based on Pauwels grade of the fracture [27].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have since shown that it is a poor predictor of non-union [25]. However, others, such as the study by Zhu et al [26], have found it useful in predicting reoperation after initial fixation. The Dutch Surgical Society guidelines for the treatment of femoral neck fractures are based on Pauwels grade of the fracture [27].…”
Section: Discussionmentioning
confidence: 99%
“…Three cannulated screws are inserted in a parallel inverted triangle configuration (inferior, posteromedial, and anterosuperior) because they can provide high mechanical stability. [11][12][13][14][15] Moreover, surgeons usually place the cannulated screws tightly on the posteromedial cortex and try to keep the screws inside the cortical bone, which provides better support and stabilization of the fracture area. 16,17 For fracture repositioning and fixation stability, surgeons place cannulated screws as close to the posteromedial cortex as possible; however, this operation is often performed using intraoperative fluoroscopy and is based on their own experience.…”
Section: Introductionmentioning
confidence: 99%
“…Three cannulated screws are inserted in a parallel inverted triangle configuration (inferior, posteromedial, and anterosuperior) because they can provide high mechanical stability. 11 , 12 , 13 , 14 , 15 Moreover, surgeons usually place the cannulated screws tightly on the posteromedial cortex and try to keep the screws inside the cortical bone, which provides better support and stabilization of the fracture area. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%